Clay-cement additive for crushed rock base stabilisation: Strength property investigation - Jitsangiam, Peerapong; Merrin, M.; Kumlai, S. (The Geomate International Society, 2016)
With the current base course material in Western Australia, namely hydrated cement treated crushed rock base (HCTCRB), roads using HCTCRB require excessive maintenance causing from its uncertainties. This study aims to determine specific strength properties of a potential replacement material of a clay - cement stabilized crushed rock. The findings showed that a crushed rock material with a newly developed 3% clay - cement binder, possessed unconfined compressive strengths and resilient moduli significantly greater than that of HCTCRB . The developed stress dependent equation also purports that this material admixture is still exhibiting unbound performance characteristics. A material’s ability to acquire the accompanying strength advantages of a 3% clay - cement binder, whilst still potentially resisting common failure methods such as shrinkage cracking, suggests that based on its potential performance as a base course layer in a pavement structure, clay - cement stabilized crushed rock base is considerable to be a viable base course material for Western Australia.